1969
DOI: 10.1159/000196942
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Aspects of the Liver in the Viral Hepatitis

Abstract: The ultrastructure of the liver cells during viral hepatitis is presented. The character of the noticed disturbances is variable with a rather patchy distribution, without any specificity of this disease. On the contrary remarkable and original patterns were observed at the level of the intercellular spaces; an important process of winding; presence of electronopaque grains (probably formed of biliary pigments), dilatation of the intercellular spaces between junctional complexes; joining of the cellular membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1970
1970
1981
1981

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…13, 22J, of tissues infected with Coxsackie virus B, (12), and of L cells infected with Mengovirus (1,2). Similar changes also have been described in human viral hepatitis [33], Some of the vesicles which contain condensed cytoplasm appear to re present cisternae of endoplasmic reticulum. From this and previous studies it seems that vésiculation and vacuolization are consequences of mem brane proliferation and that this phenomenon is a host cell-virus inter action common to many viral infections, but specifically related to in fections with the picornaviruses [22], Furthermore, it is suggested that this phenomenon is an early cellular response that may precede more pro nounced degenerative changes which may be detected by light microscopy.…”
Section: Discussionsupporting
confidence: 75%
“…13, 22J, of tissues infected with Coxsackie virus B, (12), and of L cells infected with Mengovirus (1,2). Similar changes also have been described in human viral hepatitis [33], Some of the vesicles which contain condensed cytoplasm appear to re present cisternae of endoplasmic reticulum. From this and previous studies it seems that vésiculation and vacuolization are consequences of mem brane proliferation and that this phenomenon is a host cell-virus inter action common to many viral infections, but specifically related to in fections with the picornaviruses [22], Furthermore, it is suggested that this phenomenon is an early cellular response that may precede more pro nounced degenerative changes which may be detected by light microscopy.…”
Section: Discussionsupporting
confidence: 75%